Cervical laminoplasty: description of the technique and bibliographic review - RANC, Revista Argentina de Neurocirugia; Vilariño, Augusto; Erice, Santiago; Sainz, Ariel; Seclen, Daniel; Luque, Leopoldo Luciano (Revista Argentina de Neurocirugía, 2024)
Background: laminoplasty is a spinal cord decompression technique, through the enlargement of the spinal canal, with preservation of the posterior spinal elements.Objectives: to present a case series of 80 patients treated with “open door” laminoplasties, to describe the surgical technique employed and to analyze the current literature.Methods: 80 patients with multisegmented cervical canal narrowing that failed to respond to conservative measures underwent surgical treatment with “open door” laminoplasty between 2013-2019. We analyze demographic and intraoperative data; clinical outcomes were evaluated using the Nurick scale.Results: 80 patients received surgical treatment with “open door” laminoplasty; 38 women and 42 men, between the ages of 43 and 83; 74 patients had surgery at 5 different cervical levels; the most frequent levels were C3-C7. The mean duration of surgery was 91 minutes; the average pre-operative and post-operative scores in the Nurick scale were Median = 3 (IQR 3-4) and Median = 1 (IQR 1-3) with a p
Keywords: Cervical decompression; Cervical laminoplasty; Myelopathy; Open door laminoplasty